Lipid profiles in hemodialysis and nonhemodialysis patients with chronic renal insufficiency (Annals of Medical Research, 2021)
In this study, plasma concentrations of total cholesterol (TC), triglycerides (TG), high density lipoprotein cholesterol (HDL-C), low density li/x)protein cholesterol (LDL-C). apolipoprotein A-I (Apo A-l) and B (Apo B), and the ratios of HDL-C to TC, HDL-C to LDL-C and Apo A-I to Apo B in 38 hemodialysis and 30 predialvsis patients were compared with the concentrations and ratios in 34 healthy subjects.The highest plasma TC. HDL-C' TC . HDL-C/ LDL-C, and Apo A-L Apo B ratios in both of the patient gruops. As a result, these data show that patients who undergo regular hemodialysis show tendency of atherosclerotic disease development.
Keywords: Atherosclerosis, hemodialysis, lipoprotein.